Prevalence of surgical site infections in Gulf Cooperation Council countries: A systematic review and meta-analysis - Seba T. Al-Gunaid; Derren DCH. Rampengan; Jomana B. Khadra; Aya T. Elgohari; Rim M. Mouzhir; Abdulrahman A. Alzahrani; Mousab MAH. Osman; Zahra A. Alabbad; Muhammad A. Adista; Sami A. Al-Dubai; Layan K. Aleid (Narra Sains Indonesia, 2026)
Surgical site infections (SSIs) rank among the most prevalent healthcare-associated infections, leading to higher patient morbidity, extended hospitalizations, and increased healthcare expenses. Despite advancements in surgical practices within the Gulf Cooperation Council (GCC) nations, information on SSI prevalence remains fragmented and inconsistent. The aim of this study was to determine the overall prevalence of SSIs in GCC countries and to assess variations according to surgical procedure type. A systematic search of PubMed, PubMed Central (PMC), ScienceDirect, and Google Scholar was conducted for studies reporting SSI prevalence in the six GCC countries up to May 2025. The quality of the study was evaluated using the Newcastle-Ottawa Scale. Pooled prevalence estimates were calculated using a random effects model, with subgroup analyses performed based on surgical procedure type. A total of 23 studies involving 32,366 patients were included in the analysis. The overall pooled prevalence of SSIs was 7% (95%CI: 4–10%; I²=92.9%), which suggests a significant level of variability. The highest SSI prevalence was observed in coronary artery bypass graft (CABG) procedures (42%), followed by colorectal surgeries (28%) and coronary artery surgeries (18%). Lower prevalence rates were reported for laparotomies (2%) and cholecystectomies (1%). Caesarean section, the most frequently reported procedure (n=12,419), had an SSI prevalence of 3% (95%CI: 2–4%; I²=84.5%). Smaller studies tended to report higher SSI prevalence estimates. In conclusion, the elevated incidence of SSIs in high-risk procedures, particularly CABG and colorectal surgeries, highlights the necessity for enhanced regional surveillance systems and targeted preventive measures across GCC healthcare settings.